(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
No doubt the ends of the centuries are terrifying for some people; For others, however, they represent the almost metaphysical passage to another world, to a better future, to a new life, or a new story. The fact that the belief in awakening to a new history is accepted is a product of the teleological vision of temporality that, in our case, is not offered by Judeo-Christian culture, which leaves the passage from one life to another laid at its foundations.